The discipline that 'became': Developments in Music Technology in British higher education between 2007 and 2018. Issue 3 (1st December 2018) - Boehm, Carola; Hepworth-Sawyer, Russ; Hughes, Nick; Ziemba, Dawid
In 2007 Carola Boehm published the introductory article within the first volume of the Journal of Music, Technology and Education entitled 'The discipline that never was: Current developments in Music Technology in higher education in Britain'. Boehm identified the higher education (HE) offerings in Music Technology at that time. In the ten or so years that have passed since those findings, we have witnessed both incredible growth in the HE sector and significant shift in the flavour of programmes on offer. This shift has been seen primarily in the growth of the creative practice-led title of 'Music Production', but not at the expense of traditional 'Music Technology'. Boehm's paper also explored the wider range of subject matters that could be considered within the then term 'Music Technology', whether by an ever-expanding technological backdrop, or through interdisciplinarity. In this article, we report on the significant changes since then, with some analysis for the future whilst considering the current political challenges for British HE.